2021
DOI: 10.3389/fpsyg.2021.657791
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Constructing College Students' Entrepreneurial Value Judgments Based on Educational Psychology

Abstract: Against the background of economic globalization, the strategies for constructing college students' entrepreneurial value judgment are explored, providing college graduates with more employment options and thereby keeping up with the trend of the times. The documentary analysis and questionnaire survey methods are adopted to investigate contemporary college students' entrepreneurial value judgments, and the investigation results are organized. According to documentary materials, the discovered problems are ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…"Collaborative Approaches": Collaborative networks and partnerships between educational institutions, industry, and government are essential for promoting innovation and entrepreneurship in higher education. Building strong relationships and cooperation can facilitate the diffusion of innovative practices (Zhen et al, 2021;Xu, 2023;Rii et al, 2022).…”
Section: Theory Of Model Integrated Learning On the Adoption And Diff...mentioning
confidence: 99%
“…"Collaborative Approaches": Collaborative networks and partnerships between educational institutions, industry, and government are essential for promoting innovation and entrepreneurship in higher education. Building strong relationships and cooperation can facilitate the diffusion of innovative practices (Zhen et al, 2021;Xu, 2023;Rii et al, 2022).…”
Section: Theory Of Model Integrated Learning On the Adoption And Diff...mentioning
confidence: 99%
“…The "Theory of Planned Behavior" by Ajzen, adapted to the data science context, highlights the importance of individual attitudes, subjective norms, and perceived behavioral control in influencing entrepreneurial intentions within the data science sector [17]. According to the adapted theory, an individual's attitude towards data-driven entrepreneurship and the expectations of others has a significant impact on shaping their entrepreneurial intentions within the data science field [18]. Moreover, the individual's perception of their capability to exert control over entrepreneurial activities in the data science domain (perceived behavioral control) also plays a crucial role in shaping the process of intention formation [19].…”
Section: Influence Of Multiple Factors On Entrepreneurial Intentions ...mentioning
confidence: 99%
“…The results showed that college students with higher education had higher integrity and entrepreneurship, which had a positive impact on the performance of enterprises ( Zhang et al, 2021 ). Given the lack of entrepreneurship education from the perspective of educational psychology, many scholars have proposed solutions, such as building a value judgment system for college students ( Chen et al, 2021 ) and strengthening the cultivation of cultural diversity ( Li Z. J. et al, 2021 ). In addition, many researchers from the direction of educational psychology, the entrepreneur and employee characteristics of the empirical analysis and comparison ( Yuan et al, 2020 ; Yuan and Wu, 2020 ), cover a number of promising industries such as instant messaging and barrier-free transportation ( Wu et al, 2020 ; Yuan et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%